(untitled) (Eurasian Research Bulletin, 2023)
The pathogenesis of kidney damage in SARS-CoV-2 infection is multifactorial. First, SARS-CoV-2 may have a direct cytopathic effect on the kidney. This is confirmed by the detection of coronavirus fragments by polymerase chain reaction in the urine of patients infected with COVID-19 [5]. Purpose: to assess partial kidney function in children with pyelonephritis against the background of COVID-19